2015
DOI: 10.1111/adb.12268
|View full text |Cite
|
Sign up to set email alerts
|

(R)-Salsolinol, a product of ethanol metabolism, stereospecifically induces behavioral sensitization and leads to excessive alcohol intake

Abstract: Ethanol is oxidized in the brain to acetaldehyde, which can condense with dopamine to generate (R/S)-salsolinol [(RS)-SAL]. Racemic salsolinol [(RS)-SAL] is self-infused by rats into the posterior ventral tegmental area (VTA) at significantly lower concentrations than those of acetaldehyde, suggesting that (RS)-SAL is a most active product of ethanol metabolism. Early studies showed that repeated intraperitoneal or intra-VTA administration of (RS)-SAL (10 mg/kg) induced conditioned place preference, led to loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 37 publications
3
36
0
Order By: Relevance
“…Studies by Quintanilla et al (2016a), in UChB rats showed that the intra-cerebroventricular or systemic administration of ( R/S) -SAL increased the motivational effects of ethanol as shown by the place preference technique (Figure 5), in line with studies by Matsuzawa et al (2000) in Sprague-Dawley rats and by Hipólito et al (2011) in Wistar rats.…”
Section: Acquisition Of Ethanol Intakesupporting
confidence: 81%
See 1 more Smart Citation
“…Studies by Quintanilla et al (2016a), in UChB rats showed that the intra-cerebroventricular or systemic administration of ( R/S) -SAL increased the motivational effects of ethanol as shown by the place preference technique (Figure 5), in line with studies by Matsuzawa et al (2000) in Sprague-Dawley rats and by Hipólito et al (2011) in Wistar rats.…”
Section: Acquisition Of Ethanol Intakesupporting
confidence: 81%
“…This effect was also observed by Myers and Melchior (1977) in Sprague-Dawley rats. Noteworthy, the high ethanol intakes are of the same order as those ingested by rats that had consumed ethanol for several weeks and were exposed to the ethanol deprivation condition followed by ethanol re-access ( vide infra ).Studies by Quintanilla et al (2016a), in UChB rats showed that the intra-cerebroventricular or systemic administration of ( R/S) -SAL increased the motivational effects of ethanol as shown by the place preference technique (Figure 5), in line with studies by Matsuzawa et al (2000) in Sprague-Dawley rats and by Hipólito et al (2011) in Wistar rats.Intracerebral administration studies in UChB rats showed that the ethanol motivational and intake sensitization effects of ( R/S) -SAL is also seen with R-SAL while the S-SAL enantiomer is inactive (Figure 6; Quintanilla et al, 2016a). Although the pharmacological mechanisms responsible for the action of (R/S )-SAL remain unclear, the specific effect of the R-enantiomer in inducing the motivational effects of ethanol, suggests that in vivo the chirality of the C-1 center of (R/S )-SAL plays an important role in changing its affinity for transporters or receptors associated with ethanol intake.…”
Section: Acquisition Of Ethanol Intakementioning
confidence: 99%
“…An animal study performed in alcohol-preferring P rats showed that after 8 weeks of chronic ethanol consumption, there was a 2-fold increase in (S)-SAL levels in the midbrain, whereas a 1.6-fold increase was detected in (R)-SAL levels (Rojkovicova et al, 2008). In contrast to these findings, a recent behavioral study by Quintanilla et al (2016) found that (R)-SAL was the only enantiomer capable of inducing conditioned place preference after its intracerebral infusion into the VTA of rats. The reasons for these inconsistencies are unknown, but a possible explanation would be the existence of different molecular targets for (R)-SAL or its in vivo metabolism.…”
Section: Discussionmentioning
confidence: 78%
“…(R)-SAL and (S)-SAL were separated from the racemic solution by high-pressure liquid chromatography (HPLC) as described previously (Quintanilla et al, 2016). Briefly, a solution of (R/S)-SAL was injected into a NUCLEODEX β-cyclodextrin-modified column (Macherey-Nagel, Düren, Germany) kept at 20°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation